2018
DOI: 10.7708/ijtte.2018.8(2).03
|View full text |Cite
|
Sign up to set email alerts
|

Designing the Appropriate Data Collection Method for Public Transport Passenger Satisfaction Analysis

Abstract: Abstract:Incessantly increasing urbanization is a threat to mobility, environment and ultimately to the quality of life. Promoting public transport in the major cities seems to be a promising solution to this issue which can be achieved by moving toward attracting more satisfied public transport passengers (PTP). The first step in PTP satisfaction analysis is collecting the reliable data which is equally suitable for all passenger groups (i.e. handicapped, visually impaired, etc.) in order to limelight the mos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…The satisfaction of public transport users is heavily influenced by onboard experience where it can only be beneficial if the service provided is reliable [48,49]. This is proven in the past study indicating that the commuters travelling with unreliable public transport have lower satisfaction than those who travelled with reliable public transport [50].…”
Section: Reliabilitymentioning
confidence: 97%
See 1 more Smart Citation
“…The satisfaction of public transport users is heavily influenced by onboard experience where it can only be beneficial if the service provided is reliable [48,49]. This is proven in the past study indicating that the commuters travelling with unreliable public transport have lower satisfaction than those who travelled with reliable public transport [50].…”
Section: Reliabilitymentioning
confidence: 97%
“…Comfort may refer to one's pleasant or relaxing feeling to the environment [52]. It is one of the important variables in measuring the quality and preference of public transport users [49,53]. Both physical comforts of the vehicle and ambience comfort on board or at the waiting point have to be taken into consideration to measure public transport comfortability.…”
Section: Comfortmentioning
confidence: 99%
“…A crucial aspect of the worldwide drive to achieve transportation sustainability is public transport, which also plays a vital role in the vibrancy of the economy and supports the general well-being of the population. This concept is an advanced alternative with which to overcome environmental and quality-of-life problems such as air pollution, noise pollution, accidents and traffic congestion [1][2][3][4][5]. The evidence of this is derived from Wall et al [6], who reported that CO 2 and NO X emissions per mile, as well as traffic congestion, reduced when people used sustainable modes of transportation, such as public transport in city centres.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Kwan et al [4] stated that Kuala Lumpur had an 83% private transport use rate, while public transportation was used by 17%. Relying so extensively on private transport has several negative effects: environmental conditions and the quality of life are adversely impacted, while it also leads to busier roads, polluted air, noisy conditions, and traffic accidents [5][6][7][8][9]. According to Mouwen [8], transport is responsible for 40% of the emissions of carbon dioxide and over 70% of different pollutant types.…”
Section: Introductionmentioning
confidence: 99%